One and done: Examining the relationship between years of college basketball experience and career statistics in the National Basketball Association - Zestcott, C. A.; Dickens, J.; Bracamonte, N.; Stone, J.; Harrison, C. K. (Journal of Sport and Social Issues, 2020)
Since 2006, the so-called one and done rule prevents American high school players from joining the National Basketball Association (NBA) without at least 1 year of college basketball experience. While there is debate about the pros and cons of the one and done rule, few studies have fully examined how minimal (or no) college experience relates to performance in the NBA. The current study used publicly available offensive and defensive statistics for all players in the NBA from 1995 to 2016, to examine the relationship between years of college experience and career success in the NBA. Results showed that players with less college experience had better offensive, defensive, and advanced metric (player efficiency rating [PER] and value over replacement player [VORP]) statistics than players with more college experience. However, players with less college experience also made more mistakes in game play, such as turnovers and fouls. The results suggest that college players may not need to attend college to succeed in the NBA.